2014
DOI: 10.1038/ajg.2014.47
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Eosinophilia is Increased in Rural Areas With Low Population Density: Results From a National Pathology Database

Abstract: Objectives Eosinophilic esophagitis (EoE) is an increasingly prevalent chronic disease arising from an allergy/immune-mediated process. Generally, the risk of atopic disease differs in rural and urban environments. The relationship between population density and EoE is unknown. Our aim was to assess the relationship between EoE and population density. Methods : We conducted a cross-sectional, case-control study of patients with esophageal biopsies in a U.S. national pathology database between January 2009 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 39 publications
1
50
0
1
Order By: Relevance
“…Th erefore, they were not extracted for the performance of this study. In the recent past, this database has been used for a large variety of histo-epidemiologic studies (3)(4)(5)(6)(7)(8). Th ese prior studies have revealed epidemiologic patterns that have been consistent with observations from diff erent databases and by other investigators.…”
Section: Data Sourcementioning
confidence: 64%
“…Th erefore, they were not extracted for the performance of this study. In the recent past, this database has been used for a large variety of histo-epidemiologic studies (3)(4)(5)(6)(7)(8). Th ese prior studies have revealed epidemiologic patterns that have been consistent with observations from diff erent databases and by other investigators.…”
Section: Data Sourcementioning
confidence: 64%
“…The third study used a large pathology database to assess population density as a risk factor for EoE. 37 14,381 EoE cases were compared to almost 90,000 controls from throughout the U.S., and the odds of EoE increased with decreasing population density. For example, comparing the least to most dense quintile of population density, the aOR was 1.59 (95% CI 1.45-1.76).…”
Section: Resultsmentioning
confidence: 99%
“…8,37,38,41,42,45,47-49,51,52 However, these studies are still at a general level, and it remains to be seen whether trends in seasonality or climate will be able to be linked to a discrete environmental factor that could impact an individual patient. A similar statement could be made for EoE being more common in areas with low population density.…”
Section: Discussionmentioning
confidence: 99%
“…The database contains demographic information, a detailed list of all results from surgical pathology reports (coded in a predefined, standardized, and searchable manner), a summary of the endoscopic report, and a synopsis of the clinical indications that led to the endoscopic procedure. In the recent past, this database has been utilized for a large variety of histoepidemiologic studies [1][2][3][4][5][6]. The Miraca Life Sciences Database was searched for all records of patients who had had a colonoscopy between 1 January 2008 and 15 August 2013 for the investigation of diarrhea.…”
Section: Data Sourcementioning
confidence: 99%